Causal Nexus Between Liquidity Creation and Bank Capital Ratio: Evidence from India. (May 2021) - Mohanty, Seba; Mahakud, Jitendra
This study investigates the interrelationship between bank capital and liquidity creation in the Indian banking sector. The sample considers 68 commercial banks (public, private and foreign banks) operating in India during the period from 1996–1997 to 2013–2014. We employ the generalised method of moments technique in a Granger causality framework and find a bidirectional relationship between bank capital and liquidity creation for the entire sample. Our results support the financial fragility–crowding-out hypothesis, which suggests that Indian banks follow a fragile financial structure to maximise liquidity creation and increase their capital ratio by crowding out deposits to limit liquidity creation. Our results also support the liquidity substitution hypothesis, which suggests that stable liabilities can be substituted for bank capital, while facing more risk. We find similar results with the whole sample regardless of ownership, size, capitalisation and periods. These findings have implications for bank managers and policymakers on formulating appropriate policy for capital and liquidity creation of commercial banks in India. JEL Codes: G20, G21, G33